Evaluating the Impacts of Subsidies on Innovation Activities in Germany - Reinhard Hujer; Dubravko Radić (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Innovations are a key factor to ensure the competitiveness of establishments as well as to enhance the growth and wealth of nations. But more than any other economic activity, decisions about innovations are plagued by failures of the market mechanism. As a response, public instruments have been implemented to stimulate private innovation activities. The effectiveness of these measures, however, is ambiguous and calls for an empirical evaluation. In this paper we make use of the IAB Establishment Panel and apply various microeconometric methods to estimate the effect of public measures on innovation activities of German establishments. We find that neglecting sample selection due to observable as well as to unobservable characteristics leads to an overestimation of the treatment effect and that there are considerable differences with regard to size class and between West and East German establishments.
Keywords: O31; C35; C14; C25; O38; 330; R&D policy; innovation; microeconometric evaluation; Forschungssubvention; Innovationspolitik; Wirtschaftspolitische Wirkungsanalyse; Innovation; Schätzung; Deutschland